Antimony telluride as a saturable absorber for generating Q-Switched and mode-locked Erbium-Doped Fiber Lasers / Zeyad Abdullateef Ibraheem Al-Dabagh - Zeyad Abdullateef, Ibraheem Al-Dabagh (2018)
In this research, passively Q-switched and mode-locked erbium-doped fiber lasers (EDFLs) were experimentally demonstrated by using Antimony Telluride (Sb2Te3) Topological Insulator (TI) as a thin film based saturable absorber (SA). Liquid phase exfoliation (LPE) method was used to fabricate the SA by embedding the Sb2Te3 into polyvinyl alcohol (PVA) film. The pulse train was achieved by using a simple laser cavity designed to generate a low threshold pump power that creates significant pulse energy and peak power. Two experiments were conducted in this study. At first, a Q-Switching pulse laser was produced at the 1530.749 nm wavelength region. The Q-switched stabilized pulse laser was established with a threshold pump power as low as 15 mW. Repetition rate of the laser increased from 27.53 to 95.06 kHz, while the pulse width decreased from 13.84 μs to 4.89 μs as the pump power was raised from 15 mW to 81mW. The maximum pulse energy of 45.87 nJ was obtained at the maximum pump power. By adding an additional single mode fiber (SMF) section into the laser cavity, the mode-locked pulse train was generated that operates at 1533.40 nm wavelength with 3 dB bandwidth of 2.7 nm. The mode-locked pulse laser was stabilized at pump power range of 71 mW to 143 mW with pulse width and repetition rate of 6.52 ps and 996 kHz, respectively. At the maximum pump power of 143 mW, the average output power, pulse energy, peak power and the signal to noise (SNR) ratio were 6.5 mW, 6.526 nJ, 1 kW and 67 dB respectively. Keywords: Q-switched, Mode-Locked, Antimony Telluride.